History of Southeast Asia : The nineteenth and twentieth centuries - Tarling, Nicholas (Cambridge University Press, 1992)
This part of the work deals with Southeast Asia between the late eightteenth century of the Christian era and World War II. The opening chapter, which is in a sense complementary to the closing chapter of the previous of the region within the frontiers of European empires. Subssequent chapter describe the political structures, the economic and social life, and the religiouns and populer culture of the region . A final chapter includes a discussion of nationalism and nationalist movements.